Implementasi Program Kampus Aman Bencana melalui Edukasi dan Simulasi Evakuasi Gempa Bumi di STIKES Hutama Abdi Husada Tulungagung: Sinergi Civitas Akademika: Mengubah Kepanikan Menjadi Kesiapsiagaan - Manggar Purwacaraka; Gathut Pringgotomo; Ossi Dwi Prasetyo; Farida Farida; Eny Masruroh; Shulhan Arief Hidayat; Intan Munawaroh (PPPM Stikes Banyuwangi, 2026)
Earthquakes are one of the natural disasters that can cause casualties and material losses if not accompanied by adequate preparedness. Higher education institutions are vulnerable to disaster emergencies; therefore, efforts to improve disaster preparedness capacity through the Disaster-Safe Campus Program are necessary. This community service activity aimed to improve participants’ knowledge, preparedness, and skills in facing earthquake disasters through education and roleplay-based emergency response simulations. The activity was conducted at STIKES Hutama Abdi Husada Tulungagung involving 87 participants consisting of 5th semester of Bachelor of Nursing, the Student Executive Board (BEM), and the Ringinpitu Village community in collaboration with Badan Penanggulangan Bencana Daerah. The methods included pre-test, disaster preparedness education, demonstrations, earthquake emergency response simulations, victim management, trauma healing, and post-test. The results showed an improvement in participants’ knowledge and skills after participating in the education and simulation activities. Most participants also stated that the activity was highly beneficial in improving their understanding and preparedness for earthquake disasters. The roleplay-based simulation provided more realistic learning experiences, enabling participants to practice self-rescue actions, victim evacuation, and disaster response coordination directly. This activity is expected to support the development of a disaster-aware culture and improve community preparedness within the campus and surrounding community.